English Drama in the Late of Victorian Period (1880-1901): Realism in Drama Genre Revival - M. Yuseano Kardiansyah (TEKNOSASTIK, 2017)
A progressive growth in literature was seen significantly during Victorian period. These decades also saw an overdue revival of drama, in which the existence of drama was started to improve when entering late of Victorian period. Along with that situation, Thomas William Robertson (1829-1871) emerged as a popular drama writer at that time besides the coming of Henrik Ibsen’s works in 1880’s. However, Robertson’s popularity was defeated by other dramatists during late of Victorian period (1880-1901), drama writer like Oscar Wilde (1854-1900). Beside Wilde, there were several well known dramatists during late of Victorian period. Dramatists as Shaw, Jones, and Pinero were also influential toward the development of drama at that time. In the discussion of English drama development, role of late Victorian period’s dramatists was really important toward the development of modern drama. Their works and efforts really influenced the triumph of realism and development of drama after Victorian period ended. Therefore, the development of drama during late of Victorian period is discussed in this particular writing, due to the important roles of dramatist such as Wilde, Shaw, Pinero, and Jones. Here, their roles to the revival of English drama and the trend of realism in the history of English literature are very important.